PENGARUH PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STAD DALAM PEMBELAJARAN FIQIH DIKELAS X IPA MA MAMBAUL ULUM MEGALUH - Faridatul Umah; M. Dzikrul Hakim Al-Ghozali (AS-SALAM, 2022)
This research is motivated by the lack of effective application of the lecture learning method in learning fiqh. The purpose of this study is to offer a STAD cooperative learning model and measure the effectiveness of the model on fiqh subjects in class X IPA MA Mambaul Ulum Megaluh. This type of research is called quantitative research. Data collection techniques and research instruments used were observation, tests (pre-test and post-test), interviews, and documentation. The data analysis techniques used are the normality test, homogeneity test, and t-test. The results of this study indicate that there is an effect of applying the STAD type of cooperative learning model in learning fiqh in class X IPA MA Mambaul Ulum Megaluh. This is evidenced by an increase in the average score of students from before using the STAD type cooperative learning model of 48.00 to after using the STAD type cooperative learning model of 78.50. besides that, it is also proven from the comparison of the value of >(-9.781 > 1.729) with a significance value of 0.000 < 0.05. it means that there is an effect of applying the STAD type of cooperative laerningmodel, namely increasing student score.